ROLE OF INOSINE PRANOBEX IN MANAGEMENT OF HPV-ASSOCIATED DISEASES: PROBLEMS AND PROSPECTIVE - V. O. Bitsadze; N. M. Khamani; N. A. Makatsariya (IRBIS LLC, 2016)
The prevalence of HPV in Russia and the world is quite high, although epidemiological data are limited because morbidity rate of papillomatosis, particularly genital warts, are not clear. The most effective method of preventing infection is vaccination against HPV infection. One of the most effective preventive measure to reduce the risk of death from HPV-related cancer diseases is a regular screening. None of the treatments of HPV infection will not totally effective and will not prevent disease transmission. In most cases, treatment is aimed at getting rid of symptoms but not cure infection. Immunomodulators for management of HPV-associated diseases could not have evidence base. Clinically proven treatment with inosine pranobex eliminates HPV to 98% cases and 3 times reduce frequency of relapses in combined therapy. Correct and complete counseling, aimed at informing the patient about the connection of HPV infection and cancer, as well as the possibility of preventing infection by timely vaccination and proper compliance are issue at present time. Isoprinosine saves a woman from the HPV, reducing the possibility of recurrence and malignancy, only when patient has complete course of therapy.